Capacity Building Needs of Home Economics Lecturers for Computer Assisted Teaching of Pattern Drafting for Entrepreneurship in South East Nigeria - Nwamaka N. Bob-Eze; D. O Arubayi (Social Education Research, 2022)
This study looked at the capacity development requirements of Home Economics teachers in South East Nigeria for computer-assisted pattern drafting training. A research question and a hypothesis guided the investigation. Ex-post facto research was used in this study. A total of 131 Home Economics lecturers from universities, polytechnics, and colleges of education in South East Nigeria were included in the study. Because of its manageable size, the complete population was investigated, so there was no sampling. The Capacity Building Needs for Computer-Assisted Teaching Questionnaire (CBNCATQ) was used for data collection. The instrument was face-validated and tested for internal consistency using the Cronbach Alpha Coefficient. Data obtained from the respondents were analyzed using the Statistical Package for Social Sciences (SPSS). Percentages, mean scores, and standard deviations were used to answer the research question, while the hypothesis was tested with a t-test at a 0.05 level of significance. The results of this study showed that training on the use of computers, ability to use various pattern drafting materials and equipment, availability of electricity to power equipment, and ability to follow basic principles of pattern drafting, among others, were capacity building needs of lecturers. Based on the findings, it was recommended, among others, that lecturers should be given opportunities for in-service training on computer usage, and workshops should be organized for the lecturers on the benefits of using computers in teaching.